2013
DOI: 10.1093/jxb/ert329
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification alleviates low-temperature effects on growth and photosynthesis of the red alga Neosiphonia harveyi (Rhodophyta)

Abstract: This study aimed to examine interactive effects between ocean acidification and temperature on the photosynthetic and growth performance of Neosiphonia harveyi. N. harveyi was cultivated at 10 and 17.5 °C at present (~380 µatm), expected future (~800 µatm), and high (~1500 µatm) pCO2. Chlorophyll a fluorescence, net photosynthesis, and growth were measured. The state of the carbon-concentrating mechanism (CCM) was examined by pH-drift experiments (with algae cultivated at 10 °C only) using ethoxyzolamide, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…The supply of DIC may have increased -antagonistically to warming -the performance of F. vesiculosus. This finding is consistent with those of Olischläger and Wiencke (2013) and Sarker et al (2013), who examined the combined effects of CO 2 and temperature on Neosiphonia harveyi (Bailey) M.-S. Kim, H.-G. Choi, Guiry & G.W. Saunders and Chondrus crispus Stackh., respectively.…”
Section: Reproduction Under Ocean Warming and Acidificationsupporting
confidence: 89%
“…The supply of DIC may have increased -antagonistically to warming -the performance of F. vesiculosus. This finding is consistent with those of Olischläger and Wiencke (2013) and Sarker et al (2013), who examined the combined effects of CO 2 and temperature on Neosiphonia harveyi (Bailey) M.-S. Kim, H.-G. Choi, Guiry & G.W. Saunders and Chondrus crispus Stackh., respectively.…”
Section: Reproduction Under Ocean Warming and Acidificationsupporting
confidence: 89%
“…The former showed that in U. rigida the composition of the phospholipids is changing following cultivation at elevated pCO 2 and attributed this finding to a potential shift in the manner of carbon uptake. Since at low temperatures both the lipid composition of membranes changes (Floreto et al 1993) and the contribution of the CCM to photosynthetic carbon supply decreases (Olischläger and Wiencke 2013b), our findings support this hypothesis. Again, the effect of elevated pCO 2 on the lipid content of S. latissima is ecotype specific, with an insensitive Arctic population and a pCO 2 -sensitive temperate population.…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, the positive effect of elevated CO 2 in the growth rate of A. esculenta has also been observed in many species of seaweeds such as the rhodophytes Lomentaria articulata (Kübler et al 1999), Hypnea spinella (Suárez-Á lvarez et al 2012) and Neosiphonia harveyi (Olischläger and Wiencke 2013), the chlorophyte U. rigida (Gordillo et al 2001) and the brown turf-forming alga Feldmannia sp. (Russell et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Since the effect of OA on growth and photosynthetic performance has shown to be species specific, with some species benefitting and some others showing inhibition or no response, it is supposed that OA might promote changes at the community level (Olischläger and Wiencke 2013).…”
Section: Introductionmentioning
confidence: 99%